SOSIALISASI INOVATIF: PENGGUNAAN PGPR ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œBIOFERTIÃƒÂ¢Ã¢â€šÂ¬Ã‚Â SEBAGAI PUPUK UNTUK BUDIDAYA SAYURAN ORGANIK - Umul Aiman; Bambang Sriwijaya; Bambang Nugroho; Warmanti Mildaryani (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2024)
PGPR "Bioferti" is a PGPR that contains a consortium of 4 bacteria, namely Azotobacter sp., Pseudomonas sp., Bacillus sp., and Pseudomonas fluorescens which can increase plant growth and yield. PGPR is a product that functions as a biofertilizer, biostimulant (stimulates growth due to the presence of ZPT), and bioprotectant. This activity aims to provide knowledge about PGPR in general and specifically PGPR "Bioferti" for vegetable cultivation. The methods used are counseling and practice/implementation of PGPR. The activity begins with providing an understanding of PGPR, types of vegetables with their nutritional content, an understanding of organic vegetables with their advantages and disadvantages, and how to cultivate organic vegetables. Apart from providing theory, the service also invited partners to practice directly by providing seeds of various vegetables and PGPR as well as organic fertilizer for cultivation in their respective yards. The results of the service activities were an increase in community knowledge about PGPR. The evaluation results show that the community is enthusiastic about using PGPR and can cultivate organic vegetables. To ensure its continuity, continuous assistance and consultation is carried out.